Malaysia awaits you at KL'98 a pre XVI Commonwealth Games cd-rom - Zurina Zainal Abidin (Kuala Lumpur : MacWorld Sdn. Bhd., 1997)
This interactive CD-ROM presents a magnet to every nature lover to begin their journey to this ancient rain forest, without being there at all
Executive producer, P.H. Chin
Narrator: Rebecca Perry
System requirements: Multimedia PC with Pentium or higher processor. Min 16 MB RAM, sound blaster or compatible sound card, double speed or higher cd-rom drive, QuickTime 2.01 for Windows 3.1 and QuickTime 2.12 for Windows 95 or greater
Keywords: Commonwealth Games